“I can’t endure it” vs. “I can handle it” - experiencing work fatigue risk for nurses: a qualitative study - Rong Pi; Yunfang Liu; Rong Yan; Yan OuYang; Wenjing Li; Zixuan Hou; Zong De; Fang Liu; Zihan He; Yuxin Mei; Suyun Li (BMC Nursing)
Abstract Background Work fatigue has become a significant challenge for nursing staff, yet there is a paucity of qualitative research that explores their lived experiences in this context. This study aims to examine clinical nurses’ experiences with work fatigue risk and to identify the hindering and facilitating factors contributing to this issue. Methods In this study with descriptive phenomenological method, semi-structured interviews with 25 nurses conducted in the meeting room of a hospital from June to August 2024. Colaizzi’s seven-step analysis method was used for data analysis. Results Three main themes with twelve subthemes were identified. The primary themes included: (1) phases of work fatigue risk experience, (2) hindering factors of work fatigue risk management, and (3) facilitating factors of work fatigue risk management. Nurses faced a combination of facilitators and inhibitors in managing work fatigue. While some nurses demonstrated a positive attitude towards their work, others showed a strong intention to leave the profession. Conclusions Our findings offer a nuanced understanding of the dynamic stages of nurses’ work fatigue experience, highlighting both hindering and facilitating factors that influence the management of work fatigue risk. Nurses encounter multiple challenges in managing work fatigue effectively, underscoring the need for comprehensive strategies. These strategies should address structural barriers while fostering individual resilience, ultimately promoting a healthier and more sustainable work environment.